Dielectrophoretic Assembly of Graphene and Electrical Characterization - AN Li-bao; LI Wen; CHANG Chun-rui (Cailiao gongcheng, 2017)
Integrating graphene into micro-and nano-devices is a critical step for its application in many fields. Graphene-a type of two-dimensional nanomaterials was assembled by dielectrophoresis(DEP) and the influence of the DEP process parameters including the magnitude of the applied voltage, the concentration of the graphene suspension, and the duration of the electric field was investigated. Results show that the quantity of the assembled graphene increases with increasing these parameter values, and the concentration of the graphene suspension is the most significant factor. I-V curve of the assembled graphene presents a good linearity and the electrical resistance of the samples ranges from several kΩ to several hundred kΩ, depending on the quantity of the assembled graphene. This indicates that there exists a high contact resistance between graphene and metal electrodes. The contact resistance of graphene can be reduced efficiently by local joule heating, and the contact resistance is reduced at its most by 47.91% when the applied voltage is 3.6V.